Assessment of respiratory function and exercise tolerance at 4–6 months after COVID‐19 infection in patients with pneumonia of different severity. Issue 2 (28th September 2022) - Pini, Laura; Montori, Rossano; Giordani, Jordan; Guerini, Michele; Orzes, Nicla; Ciarfaglia, Manuela; Arici, Marianna; Cappelli, Carlo; Piva, Simone; Latronico, Nicola; Muiesan, Maria L.; Tantucci, Claudio
Abstract: Background: The evaluation of COVID‐19 systemic consequences is a wide research field in which respiratory function assessment has a pivotal role. However, the available data in the literature are still sparse and need further strengthening. Aim: To assess respiratory function 4–6 months after hospital discharge based on lung disease severity in patients who overcome COVID‐19 pneumonia. Methods: Patients hospitalised either in the Internal Medicine Department (IMD) for moderate to severe disease or in the Intensive Care Unit (ICU) for critical disease underwent spirometry with maximal flow‐volume curve, lung volumes, lung diffusion capacity (DLCO ) and six‐minute walking test (6‐MWT). Results: Eighty‐eight patients were analysed: 40 from the IMD and 48 from the ICU. In both cohorts, there was a greater prevalence of male patients. In the IMD cohort, 38% of patients showed at least one altered respiratory parameter, while 62% in the ICU cohort did so ( P  < 0.05). Total lung capacity (TLC) and DLCO were the most frequently altered parameters: 15% and 33% from IMD versus 33% and 56% from ICU, respectively ( P  < 0.05). In IMD patients, 5% had only restrictive deficit, 22% had only lung diffusion impairment and 10% had both. In ICU patients, 6% had only restrictive deficit, 29% had only lung diffusion impairment and 27% had both ( P  < 0.05). ICU patients showed a higher frequency of abnormal 6‐MWT ( P  < 0.05). Conclusion: Lung function tests and 6‐MWT are highly informative tools for monitoring the negative consequences of COVID‐19 pneumonia, which were more frequent and more complex in patients discharged from ICU.